(untitled) (International Conference on Computers in Education, 2016)
This study explored views held by teachers in Nigeria with regards to Information and Communication Technologies (ICT) integration. This qualitative study used interview to collect data from teachers at the college of education. Results of this study indicated that teacher education programs failed to provide adequate instructional technologies and ICT facilities for class activities. Further, three major issues which appeared to affect the integration of ICT were found to be: (a) the redesigning of the curriculum and ICT policy, (b) incompetent teachers/lack of professional training in ICT delivery, and (c) insufficient ICT structures.